(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
There agrochemicals affects the metabolic processes of the target organism, thereby killing them to be eradicated. The metabolic processes of the non target organism may also be affected by these chemicals and may produce deleterious effect.’Use of pesticides in rice field also affects the immensely significant cynobacterial flora of the field. Several reports are available in which pesticides have been found to be stimulatory at lower doses (Ahmad and Venkatraman, 1973). 2, 4-D is perhaps the first herbicide to be studied for its effects on N2 fixing blue-green algae (Venkatraman and Rajyalakshmi, 1971